Strategic Planning: Challenges and Solutions - D. A. Afinogenov; E. Yu. Kochemasova; S. N. Sylvestrov (Мир новой экономики, 2019)
The purpose of the proposed article is to identify the range of challenges and their solutions related to the practice of implementation of the Federal law “On strategic planning” in 2015–2018. The authors revealed the causes of redundancy, the inconsistency of strategic planning documents, different in level and importance for public administration. We showed that the lack of interconnection of goals and criteria for their achievement at different levels of management and between ministries (departments), the lack of a generally accepted methodology for the analysis and evaluation of the implementation of strategic decisions reduces the importance of strategic planning as an important means of improving the efficiency of public administration. Particularly, we noted that the unbalanced system of strategic planning hinders the pace of economic development and weakens the country’s ability to ensure economic security. The article reveals the measures that can and ought to be taken by the state, business and institutions of civil society to overcome the barriers and difficulties of implementing strategic planning.